2005
DOI: 10.4049/jimmunol.175.9.6123
|View full text |Cite
|
Sign up to set email alerts
|

Selection of T Cell Clones Expressing High-Affinity Public TCRs within Human Cytomegalovirus-Specific CD8 T Cell Responses

Abstract: Assessment of clonal diversity of T cell responses against human CMV (HCMV), a major cause of morbidity in immunodepressed patients, provides important insights into the molecular basis of T cell immunodominance, and has also clinical implications for the immunomonitoring and immunotherapy of HCMV infections. We performed an in-depth molecular and functional characterization of CD8 T cells directed against an immunodominant HLA-A2-restricted epitope derived from HCMV protein pp65 (NLV/A2) in steady state and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

35
244
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(282 citation statements)
references
References 44 publications
35
244
2
1
Order By: Relevance
“…The basic mechanism for this affinity maturation remains incompletely understood. In contrast to immunodominant responses, which are frequently composed of one or two prevalent clonotypes with high avidity for cognate Ags (29,51,91,92), a narrowing of the TCR repertoire in TV9-specific cultures did not occur with repeated antigenic restimulation. Failure of high-avidity clonotypes to predominate may explain why TV9 responses were not detected readily during infection.…”
Section: Discussionmentioning
confidence: 76%
“…The basic mechanism for this affinity maturation remains incompletely understood. In contrast to immunodominant responses, which are frequently composed of one or two prevalent clonotypes with high avidity for cognate Ags (29,51,91,92), a narrowing of the TCR repertoire in TV9-specific cultures did not occur with repeated antigenic restimulation. Failure of high-avidity clonotypes to predominate may explain why TV9 responses were not detected readily during infection.…”
Section: Discussionmentioning
confidence: 76%
“…Crystallographic studies revealed structural constraints of TCR-pMHC interaction as responsible for the highly restricted TCR repertoire in response to these two epitopes (12,13). It has also been proposed that successive and repetitive stimulation upon chronic infection might be responsible for TCR repertoire narrowing (14,15). However, the idea of repertoire narrowing is not consensual either in experimental models or during HIV infection (16)(17)(18).…”
mentioning
confidence: 99%
“…However, the idea of repertoire narrowing is not consensual either in experimental models or during HIV infection (16)(17)(18). In addition, it has been shown that the TCR repertoire directed against a particular CMV-derived epitope remained quite heterogeneous in healthy individuals (15). Along the same line, direct sequencing of the TCR b-chain by anchored PCR on ex vivo virus-specific sorted CD8 T cells revealed that two epitopes derived from EBV and CMV were recognized by CD8 T cells exhibiting a higher degree (seven to nine clonotypes) of clonotypic diversity (19,20) indicating that the TCR repertoire during viral response might not be as restricted as thought.…”
mentioning
confidence: 99%
“…Furthermore, the high representation of some V-J combinations in humans and in humanized mice suggests a similar mechanism of selection, independently of the donor genotype and/or of the immunological history of the subject. In that regard, it is striking to note that, in the few studies that describe public TCR (T-cell clones conserved in various human afflictions among different patients), most belong to highly conserved hTRBV families that we describe here (the BV19 gene for Influenza infection [24], the BV6 family for HCMV [25] and SIV [26] infections, and the BV20 gene for EBV infection [27,28]. This correlation is not restricted to viral infections since the BV4 and BV12 families are also commonly used in autoimmune anti-phospholipid syndrome [29]).…”
mentioning
confidence: 93%
“…Regarding clustering of the hTRBV genes, three major groups were observed (Fig. 4A, vertical dendrogram): the distribution of J elements within BV15,18,25,10,29,24,30 These are not the final page numbers (C6, C12, PBMC3, PBMC5, C10, C13, C14, C4, C11, C7 and C8), the other half being closer to the mean. The second group showed perturbation in the distribution of J elements within BV16, 14 and 13 across all samples.…”
mentioning
confidence: 99%